The Effectivity of Language Games Method and Learning Motivation Toward the Language Competence of Early Children - Pusari, Ratna Wahyu; Karmila, Mila (Universitas Negeri Semarang, 2018)
Language competence is a set of knowledge, attitude and skill which absolutely belongs since a child. Because it is an asset for being able to communicate in order to understand, get information, express mind and feeling, and develop knowledge. So that, language learning through a fun method with another supporting factor, like learning motivation is expected to influence the level of the early children language competence. The goals of this research are to test the differences of language competence between a group which gets treatment of language games and the group which gets conventional method, to test the differences of language competence between group which has a high motivation and group which has a low motivation, to test the influences of interaction between language games method and learning motivation toward language competence of child. This research uses quantitative approach with experiment method factorial designed 2x2 with four kindergartens in Tembalang as the samples. Normality test uses Lilifors Test, Homogenity uses Barlet Test and hypothesis test uses ANAVA two strips with t-Dunnet test with alpha = 0.5 as the level of belief are proven that the seven hypothesis are appropriate with the goals of research which can be received. As the result, the treatment of language games method and learning motivation are effective significantly in developing children language competence.